Religious Habitus and Adaptation in Urban Pluralism: A Study of Tolerance Village, Bandung - Taufik Hidayatulloh; Theguh Saumantri; Mohd Haidhar Kamarzaman (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
Urbanization in Bandung, particularly in the Tolerance Village of Andir District, has brought significant changes in the religious practices of individuals migrating from rural areas. Previous studies on religion and urbanization often focus on institutional transformation or interreligious conflict, while limited attention has been given to the micro-dynamics of religious habitus as a sociological concept. This study aims to analyse the dynamics of religious habitus in the process of religious adaptation amidst urban religious pluralism, highlighting the Tolerance Village as a unique case. The research employed a descriptive qualitative method with a sociological approach, using in-depth interviews and observations, and data were analysed thematically. The findings show that the religious habitus of individuals undergoes transformation in response to pluralistic urban life, with the emergence of syncretic practices and adjustments to more open social norms. This adaptation process is shaped by the social and cultural capital of individuals, as well as their interactions with diverse religious communities in the Tolerance Village. The study’s novelty lies in its application of Bourdieu’s concept of habitus to explain religious adaptation in an urban pluralistic setting, thus providing a new analytical perspective for understanding the intersection of religion, migration, and urban diversity in Indonesia.